(untitled) (Journal of Science and Technology, 2016)
A solar photovoltaic power system comprises of photovoltaic modules, storage medium and elements of power conditioning. In order to design a complete power system for a particular location (say Kumasi, Ghana), data on the solar radiation at the location of the system (local isolation) are necessary. An attempt has been made to study the global solar radiation on a tilted surface using available data on a plane surface for Kumasi, Ghana. The I–V characteristics of a Photovoltaic module (12V, 24W) and that of a lead-acid battery, have been measured to determine the maximum power of the module, the state of charge of battery and also the battery sizing. From the data obtained for the panel was 1.99KW and that for the average battery capacity obtained for a month was 123KWh. However, due to the variation in location and angle tilt, the peak power changes, hence a corresponding change in the battery capacity. The results obtained from the data in this work can be used to design a stand-alone photovoltaic power system with battery storage for a particular location.